Chicago Paper - Microscopic Metallography (See Discussion, "Physics of Steel," vol. xxiii.) - F. Osmond (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1894)
When a metal (whether a simple substance, an alloy, or a compound) presents, in each of the smallest parts to which it can be redueed by mechanical division, a constant chemical composition, it is defined as chemically homogeneous. But chemical hombgeneity by no means necessitates mechanical homogeneity. There are no perfectly amorphous metals. Crystalline forces, on the one hand, and tensions or compressions, on the other band, determined by icequalities of temperature in the mass during heating or cooling, give rise in every metal to the formation of geometric elements of structure. These elements may, moreover, assume perfect crystalline forms, with their planes of cleavage; or embryonic crystalline forms, segregated in the midst of. a paste of confused organization; or pseudo-crystalline forms of expansion and contraction, like those produced in the drying of gelatinous precipitates or (most frequently) these different forms associated. 111 either case the adhesions between two adjoining structural elements, respectively homogeneous, may be very different from the interior cohesion of each of these elements. The mechanical properties of this complex aggregate cannot be simple, and, when it is submitted to strains sufficient to produce deformation, the results may be very different according to the type of structure or the manner in which it is affected by the strains. It may be fairly said that a metal does not present a single resistance to tension, or a single resistance to compression, etc., but in fact, at least theoretically, as many resistances to tension, compression, etc., as it may possess coexistent features of structure; only, in any single test, it is the weakest of the resistances involved which makes itself evident. For further explanation, let us imagine a cylinder A B (Fig. I), formed of two similar halves A and B, placed together upon their common base x y. Such a system evidently presents no resistance to axial tension, while it would resist axial compression like a single